1988
DOI: 10.1055/s-0038-1647041
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Carbohydrate Structure on the Clearance of Recombinant Tissue-Type Plasminogen Activator

Abstract: SummaryModification of the carbohydrate structures of recombinant tissue-type plasminogen activator (rt-PA) can increase or decrease its rate of clearance in rabbits. When rt-PA was treated with sodium periodate to oxidize carbohydrate residues, the rate of clearance was decreased from 9.6 ± 1.9 ml min−1 kg−1 to 3.5 ± 0.6 ml min−1 kg−1 (mean ± SD, n = 5). A similar change in the clearance of rt-PA was introduced by the use of endo-β-N-acetyl- glucosaminidase H (Endo-H), which selectively removes high mannose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
51
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(55 citation statements)
references
References 10 publications
(13 reference statements)
4
51
0
Order By: Relevance
“…These properties of insect cells are thought to be useful for the production of recombinant mammalian proteins by baculovirus-insect cell systems because the produced proteins are expected to be structurally and biologically equivalent to native ones. In addition to these posttranslational events, glycosylation (particularly N-glycosylation and terminal sialic acid modification) is important for the biological activity and stability of synthesized proteins (5)(6)(7)(8). In mammalian cells, the N-glycosylation pathway starts by the transfer of a dolichollinked precursor oligosaccharide (Glc 3 Man 9 GlcNAc 2 ) to a nascent polypeptide.…”
mentioning
confidence: 99%
“…These properties of insect cells are thought to be useful for the production of recombinant mammalian proteins by baculovirus-insect cell systems because the produced proteins are expected to be structurally and biologically equivalent to native ones. In addition to these posttranslational events, glycosylation (particularly N-glycosylation and terminal sialic acid modification) is important for the biological activity and stability of synthesized proteins (5)(6)(7)(8). In mammalian cells, the N-glycosylation pathway starts by the transfer of a dolichollinked precursor oligosaccharide (Glc 3 Man 9 GlcNAc 2 ) to a nascent polypeptide.…”
mentioning
confidence: 99%
“…Furthermore, selective digestion and chromatography, as well as sophisticated analytical techniques like mass spectrometry and high-resolution NMR spectroscopy, helped to elucidate the structures of the oligosaccharide moieties of certain recombinant proteins expressed in different eukaryotic systems Baldwin et al, 1990;Lee, 1990;Aeed et al, 1992;Edge et al, 1992;Fu & van Halbeek, 1992;Carr et al, 1993). In addition, the function and the effect of carbohydrate on physicochemical properties of several recombinant proteins, such as tissue-type plasminogen activator (Hotchkiss et al, 1988), erythropoietin (Takeuchi et al, 1990;Narhi et al, 1991), stem cell factors , and others, have been reported. Soluble forms of human and mouse interferon -y (IFNy) receptors were produced in Escherichia coli, in baculovirus-infected insect Sf9 cells, and in Chinese hamster ovary (CHO) cells (Fountoulakis et al, 1990Gentz et al, 1992).…”
mentioning
confidence: 99%
“…It is recognized by mannose receptors of hepatic endothelial cells. [50] Also, variants of t-PA with removal of the epidermal growth factor domain, prolong the circulation of the enzyme in vivo. [51] Here, the tyrosine 67 seems to be important, because replacement of this residue decreases the clearance by preventing the interaction with specific hepatic receptors.…”
Section: Anistreplasementioning
confidence: 99%
“…Alteplase (rt-PA) Human [2], [29][30][31][32][33][34][35][36][37][38][39][40], [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] Gly-Pro-Arg (GPR) at the a-chain and Gly-His-Arg (GHR) at the b-chain. They are positively charged and are called 'knobs' , leading to polymerization by non-covalent interaction with negatively charged 'holes' in the carboxy-terminal region of the g-chain (a-g) or b-chain (b-b) of other fibrin monomers.…”
Section: Second Generationmentioning
confidence: 99%